Adam Smith, America, and the Doctrinal Defeat of the Mercantile System - Fay, C. R. (Quarterly Journal of Economics, 1934)
England's rivals, 304. — Each century had its spokesman: Malynes, 305; Mun, 306; Gee and Postlethwayt, 308. — The Wealth of Nations an attack on all three, 311. — To Smith foreign trade is internal trade internationalized, 312. — Defining mercantilism as protectionism obscures the issue, 314. — Three clues to Smith's significance: his realism, his balance, his creating as he builds, 315. — The place of America in Smith's thought, 315.